A high-performance grouting material with both fluidity and strength, and preparation method and application thereof

By using the combination of sulfuric acid cement, ordinary cement, ultra -fine powder coal ash and silicon ash in the grouting material, and add alcoholic reagent and calcium aluminum acid, the existing cement grouting material is liquid at low temperature at low temperature The problem of insufficient early strength realizes the high current and high -intensity effects in low temperature environments.

CN118993670BActive Publication Date: 2025-01-24SICHUAN HIGHWAY PLANNING SURVEY DESIGN AND RESEARCH INSTITUTE LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411499215.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-24
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The existing cement-based grouting materials have poor fluidity and early strength in low-temperature environments, making it difficult to meet the needs of construction environments such as roads and railways.

Method used

The combination of sulfuric acid saline cement, ordinary cement, ultra -fine powder coal ash, and silica ash is used as a gel material, and alcoholic reagents and calcium aluminum acid are added to the grouting material. Through the combination of these combinations and additives The liquidity and early strength of materials.

Benefits of technology

At low temperatures, the grouting material has excellent fluidity and strength, especially high compressive strength within 2 hours, and is suitable for the construction of bridges and highways.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and specifically discloses a high-performance grouting material with both fluidity and strength, a preparation method and an application thereof, comprising the following components by weight: 400-500 parts of cementitious material, 500-600 parts of aggregate, 1.2-1.5 parts of water reducer, 2-2.5 parts of early strength agent, 1-1.5 parts of retarder, 2-5 parts of alcoholamine reagent, and 2-3 parts of calcium aluminate; wherein the cementitious material is composed of sulphoaluminate cement, ordinary cement, ultrafine fly ash and silica fume. The grouting material of the invention adopts a combination of sulphoaluminate cement, ultrafine fly ash and silica fume as a cementitious material, so that the grouting material has good fluidity and early strength at low temperature, and is used in combination with alcoholamine reagent and calcium aluminate to realize continuous hydration of the grouting material, and the sulphoaluminate cement releases relatively high heat during the hydration process, and continuously releases heat during the continuous hydration process, and at the same time improves the early strength and strength of the grouting material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a high-performance grouting material having both fluidity and strength, a preparation method and an application thereof. Background Art

[0002] Grouting material is a grouting material used for repairing and reinforcing reinforced concrete structures. It has the characteristics of high strength, high viscosity and high durability. It can fill the pores, cracks and damaged parts in the concrete structure, enhance the bearing capacity and durability of the structure, and is widely used in the repair, reinforcement and protection of industrial and civil buildings, such as bridges, tunnels, roads, railway dams, underground projects, etc.

[0003] Grouting materials are mainly divided into cement-based grouting materials and acrylate grouting materials according to the base material. Among them, acrylate grouting materials will release pungent odors and cause irritation to the skin and respiratory system, which is not friendly to construction. The fluidity and early strength of cement-based grouting materials are relatively poor. For the grouting of post-tensioned prestressed bridges and large prestressed structural channels of highways and railways, the grouting materials are required to have excellent fluidity and early strength, and still have excellent fluidity and early strength at low temperatures, because there are some low-temperature environments in the construction environment of roads and railways.

[0004] Therefore, in order to adapt to the grouting of post-tensioned prestressed bridges and large prestressed structural ducts on roads and railways, it is necessary to improve the existing cement-based grouting materials to improve the fluidity and early strength of the grouting materials. Summary of the invention

[0005] The object of the present invention is to provide a high-performance grouting material having both fluidity and strength, wherein the grouting material has excellent fluidity and strength at low temperature.

[0006] In addition, the present invention also provides the above grouting material and a preparation method and application thereof.

[0007] The present invention is achieved through the following technical solutions:

[0008] A high-performance grouting material with both fluidity and strength, comprising the following components in parts by weight:

[0009] 400-500 parts of cementitious materials, 500-600 parts of aggregates, 1.2-1.5 parts of water reducing agent, 2-2.5 parts of early strength agent, 1-1.5 parts of retarder, 2-5 parts of alcoholamine reagents, 2-3 parts of calcium aluminate;

[0010] The cementitious material is composed of sulphoaluminate cement, ordinary cement, ultrafine fly ash and silica fume; the particle size of the ultrafine fly ash is 1 to 5 microns.

[0011] The components of existing cement-based grouting materials are mainly ordinary cement, aggregate, water reducer, early strength agent and coagulant. Although they can meet the grouting needs of concrete pores and channels at room temperature, their fluidity is poor at low temperatures (-5 to -10°C) and cannot meet the grouting needs.

[0012] The difference between the present invention and the existing cement-based grouting material is that:

[0013] First of all, the present invention not only uses ordinary cement as the cementitious material of the grouting material, but the cementitious material of the present invention is composed of sulphoaluminate cement, ordinary cement, ultrafine fly ash and silica fume, wherein the main component of sulphoaluminate cement is calcium sulphoaluminate, which is a fast-hardening cement that can obtain higher strength in a short time, has excellent corrosion resistance and high temperature resistance, and can significantly improve the early strength and durability of cement; and, sulphoaluminate cement can release higher heat during the hydration process to adapt to low temperature environment.

[0014] Among them, silica fume can improve the early strength (2-4h) of the grouting material to a certain extent. The use of silica fume in combination with sulphoaluminate cement can improve the early strength of the grouting material.

[0015] Among them, ultrafine fly ash can improve the fluidity of grouting materials.

[0016] Although the combined use of silica fume and sulphoaluminate cement can improve the early strength of the grouting material, the addition of silica fume will reduce the fluidity of the grouting material. Therefore, the present invention uses sulphoaluminate cement, ordinary cement, ultrafine fly ash and silica fume in combination to achieve better fluidity and early strength of the grouting material.

[0017] Secondly, the grouting material of the present invention also contains alcoholamine reagents and calcium aluminate. Among them, the alcoholamine reagents can reduce the surface tension of the grouting material system, accelerate the wetting and penetration of water in the system to cement particles, make the gel layer of cement particles peel off continuously, and destroy the hydrate layer of calcium sulfoaluminate and the like formed on the surface of clinker particles in the early stage of hydration, so that cement can be hydrated quickly and continuously.

[0018] Among them, calcium aluminate can accelerate the coagulation and hardening process of cement in the grouting material system, thereby promoting the penetration of water into cement particles; and the combined use of alcoholamine reagents and calcium aluminate can further accelerate the continuous hydration of cement, while sulphoaluminate cement releases relatively high heat during the hydration process, that is, the present invention uses a combination of alcoholamine reagents and calcium aluminate to cooperate with sulphoaluminate cement, which continuously releases heat during the continuous hydration process to better adapt to low temperature environments.

[0019] In addition, the continuous hydration reaction of cement causes the strength of the grouting material to increase rapidly in the initial stage, that is, it has a high early strength; and as time goes by, the continued hydration reaction will cause the strength of the grouting material to gradually increase, which can enhance the strength and durability of the grouting material 28d.

[0020] In summary, the grouting material of the present invention has excellent fluidity and strength at low temperatures, and in particular, the grouting material of the present invention has high strength after 2 hours, and is particularly suitable for the construction of bridges and roads.

[0021] Specifically, the alcoholamine reagents include diethanolamine, triethanolamine, ethanolamine and methanolamine, and when used, at least one of diethanolamine, triethanolamine, ethanolamine and methanolamine is included.

[0022] In a preferred embodiment, the weight ratio of sulphoaluminate cement, ordinary cement, ultrafine fly ash and silica fume in the cementitious material is (28-41):(7-10):(2-3):1.

[0023] If the proportion of sulfoaluminate cement in cementitious materials is too low, the 2h compressive strength will be reduced. However, if the proportion of sulfoaluminate cement in cementitious materials is too high, the 24h compressive strength will be reduced. By adding an appropriate proportion of silica fume, the 2h compressive strength and 24h compressive strength can be met at the same time. Under the premise that the amount of sulfoaluminate cement and ordinary cement is determined, if the amount of silica fume is too small, the 2h compressive strength will be reduced. If the amount of silica fume is too much, although the 2h compressive strength is high, the fluidity will be poor. The addition of ultrafine fly ash can alleviate the problem of poor fluidity of the grouting material caused by the addition of silica fume. Therefore, it is necessary to reasonably control the weight ratio of sulfoaluminate cement, ordinary cement, ultrafine fly ash and silica fume.

[0024] The present invention adopts the above-mentioned proportion of sulphoaluminate cement, ordinary cement, ultrafine fly ash and silica fume, so that the grouting material has excellent fluidity, 2h compressive strength and 24h compressive strength.

[0025] In a preferred embodiment, rubber powder is also included.

[0026] Rubber powder is obtained by crushing and screening silicone rubber or natural rubber, and the particle size of rubber powder is usually between tens of microns and hundreds of microns.

[0027] The present invention can improve the impact resistance, elasticity and toughness of the grouting material by adding rubber powder into the grouting material, and can improve the fluidity of the grouting material to a certain extent, so that the grouting material can be better used for grouting holes and pores of roads, bridges and the like.

[0028] In a preferred embodiment, the amount of rubber powder added is 1.2-1.5% of the weight of the gelling material.

[0029] Although the addition of rubber powder can improve the impact strength of the grouting material, it will affect the compressive strength. The above-mentioned amount of rubber powder added can not only improve the impact strength of the grouting material, but also will not have a significant impact on the compressive strength of the grouting material.

[0030] In a preferred embodiment, the rubber powder is modified rubber powder modified with a silane coupling agent; wherein the rubber powder is powder obtained by pulverizing waste tires.

[0031] Compared with unmodified rubber powder, modified rubber powder has better compatibility and bonding strength with grouting materials.

[0032] In a preferred embodiment, the early strength agent is calcium formate.

[0033] Calcium formate is weakly acidic when ionized in water, so it can lower the pH value in the system, accelerate the hydration of (cement particles) C3S, and speed up the coagulation and hardening of cement.

[0034] In a preferred embodiment, the water reducing agent includes a naphthalene-based water reducing agent.

[0035] In a preferred embodiment, the aggregate is quartz sand, which includes coarse sand and fine sand. The particle size of the coarse sand is 2.0-2.5 mm, the particle size of the fine sand is 0.5-0.8 mm, and the weight ratio of the coarse sand to the fine sand is 1:(0.3-0.5).

[0036] The packing density of aggregate affects the strength of the grouting material. The strength of the grouting material can be improved by reasonably setting the particle size and weight ratio of coarse sand and fine sand.

[0037] A method for preparing a high-performance grouting material comprises the following steps:

[0038] S1. Mix ultrafine fly ash, silica fume, aggregate and early strength agent to obtain material A;

[0039] S2, mixing sulphoaluminate cement and calcium aluminate evenly, adding them to material A, mixing evenly, to obtain material B;

[0040] S3, adding water reducing agent and retarder to material B and mixing evenly to obtain material C;

[0041] S4. Add the alcohol amine reagent to material C and mix evenly to obtain a high-performance grouting material.

[0042] The invention discloses an application of a high-performance grouting material, wherein the high-performance grouting material is used for grouting of concrete structures at -5 to -10°C, in particular for grouting of holes in bridges and roads.

[0043] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0044] 1. The grouting material of the present invention adopts a combination of sulphoaluminate cement, ordinary cement, ultrafine fly ash and silica fume as a cementitious material, so that the grouting material has good fluidity and early strength at low temperatures, and is used in combination with alcohol amine reagents and calcium aluminate to achieve continuous hydration of the grouting material. Sulphoaluminate cement releases a relatively high amount of heat during the hydration process, and continuously releases heat during the continuous hydration process, while improving the early strength and 28d strength of the grouting material.

[0045] 2. Adding a certain amount of rubber powder to the grouting material of the present invention can improve the impact strength of the grouting material, so that the grouting material can be better applied to the grouting of the holes of bridges and roads. DETAILED DESCRIPTION

[0046] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. The schematic implementation mode of the present invention and its description are only used to explain the present invention and are not intended to limit the present invention. The embodiments described below are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0047] In the following description, a large number of specific details are set forth in order to provide a thorough understanding of the present invention. However, it is apparent to those of ordinary skill in the art that these specific details do not have to be employed to practice the present invention. In other embodiments, in order to avoid confusing the present invention, known structures, materials or methods are not specifically described. The materials, instruments and reagents used in the following examples, unless otherwise specified, can be obtained from commercial sources. The technical means used in the examples, unless otherwise specified, are conventional means well known to those skilled in the art.

[0048] In order to improve the fluidity and strength of the grouting material at low temperatures (-5 to -10°C), this embodiment provides a high-performance grouting material having both fluidity and strength, comprising the following components in parts by weight:

[0049] 400-500 parts of cementitious materials, 500-600 parts of aggregates, 1.2-1.5 parts of water reducing agent, 2-2.5 parts of early strength agent, 1-1.5 parts of retarder, 2-5 parts of alcoholamine reagents, 2-3 parts of calcium aluminate;

[0050] The cementitious material is composed of sulphoaluminate cement, ordinary cement, ultrafine fly ash and silica fume; the particle size of the ultrafine fly ash is 1 to 5 microns. Preferably, the weight ratio of sulphoaluminate cement, ordinary cement, ultrafine fly ash and silica fume in the cementitious material is (28 to 41): (7 to 10): (2 to 3): 1.

[0051] The alcoholamine reagent includes at least one of diethanolamine, triethanolamine, ethanolamine and methanolamine.

[0052] The retarder includes at least one of sodium chloride, sodium sulfate, sodium carbonate and sodium lignin sulfonate.

[0053] The grouting material of this embodiment adopts a combination of sulphoaluminate cement, ordinary cement, ultrafine fly ash and silica fume as cementitious materials, so that the grouting material has good fluidity and early strength at low temperatures, and is used in combination with amine reagents and calcium aluminate to achieve continuous hydration of the grouting material. Sulphoaluminate cement releases a relatively high amount of heat during the hydration process, and continuously releases heat during the continuous hydration process, which will improve the early strength and 28d strength of the grouting material.

[0054] In order to improve the impact resistance of the grouting material, the grouting material of this embodiment further includes rubber powder. By adding a certain amount of rubber powder, the impact resistance of the grouting material is improved under the premise of having little effect on the compressive strength of the grouting material. Specifically, the amount of rubber powder added is 1.2-1.5% of the weight of the cementitious material.

[0055] Preferably, the rubber powder is modified rubber powder obtained by modification with a silane coupling agent, wherein the rubber powder is powder obtained by pulverization of waste tires. The specific modification process is:

[0056] First, the rubber powder prepared from waste tires is pretreated: it is soaked and ground with sodium hypochlorite solution, and then dried to oxidize the double bonds, methylene and other active groups in the rubber powder prepared from waste tires into hydroxyl, carbonyl and carboxyl groups. A certain mass of silane coupling agent KH550 is weighed, and 0.5% KH550 solution (silane coupling agent solution) is prepared with water as the solvent; then the pretreated rubber powder is added to the silane coupling agent solution and stirred evenly. The solid-liquid ratio of the coupling agent modification is 200g of rubber powder and 2L of silane coupling agent solution. Finally, it is placed in a dry environment until the surface of the rubber powder particles is completely dry.

[0057] The reaction principle of silane coupling agent KH550 and hydroxy silicone rubber is:

[0058] The pretreated rubber powder contains active groups such as hydroxyl (-OH). The silane coupling agent KH550 is hydrolyzed in water to produce silanol, which reacts with the -OH in the rubber powder.

[0059] Preferably, the early strength agent is calcium formate. Calcium formate is weakly acidic when ionized in water, so it can reduce the pH value in the system, accelerate the hydration of (cement particles) C3S, and speed up the coagulation and hardening of cement.

[0060] Preferably, the water reducing agent includes a naphthalene-based water reducing agent.

[0061] Preferably, the aggregate is quartz sand, which includes coarse sand and fine sand. The particle size of the coarse sand is 2.0-2.5 mm, the particle size of the fine sand is 0.5-0.8 mm, and the weight ratio of the coarse sand to the fine sand is 1:(0.3-0.5).

[0062] The preparation method of the high-performance grouting material of this embodiment comprises the following steps:

[0063] S1. Mix ultrafine fly ash, silica fume, aggregate and early strength agent to obtain material A;

[0064] S2, mixing sulphoaluminate cement and calcium aluminate evenly, adding them to material A, mixing evenly, to obtain material B;

[0065] S3, adding water reducing agent and retarder to material B and mixing evenly to obtain material C;

[0066] S4. Add the alcohol amine reagent to material C and mix evenly to obtain a high-performance grouting material.

[0067] The high-performance grouting material of this embodiment can be used for grouting of concrete structures at -5 to -10°C, especially for grouting of holes and gaps in roads and bridges.

[0068] The strengths not specified in this embodiment refer to compressive strength.

[0069] In order to better illustrate the effect of this embodiment, the following specific case is used for illustration.

[0070] Embodiment 1:

[0071] A high-performance grouting material with both fluidity and strength, composed of the following components in parts by weight:

[0072] 450 parts of cementitious materials, 550 parts of aggregates, 1.2 parts of naphthalene-based water reducer, 2 parts of calcium formate, 1.2 parts of sodium sulfate, 4 parts of diethanolamine, and 3 parts of calcium aluminate;

[0073] Wherein, the cementitious material is composed of sulphoaluminate cement, ordinary cement, ultrafine fly ash and silica fume; the weight ratio of sulphoaluminate cement, ordinary cement, ultrafine fly ash and silica fume is 40:10:3:1; the particle size of ultrafine fly ash is 1 to 5 microns. Preferably, in the cementitious material;

[0074] The aggregate is quartz sand, which includes coarse sand and fine sand. The particle size of the coarse sand is 2.0-2.5 mm, the particle size of the fine sand is 0.5-0.8 mm, and the weight ratio of the coarse sand to the fine sand is 1:0.4.

[0075] Embodiment 2:

[0076] This embodiment is based on Embodiment 1, and the difference from Embodiment 1 is that the dosage of each component in the high-performance grouting material is different, as follows:

[0077] A high-performance grouting material with both fluidity and strength, composed of the following components in parts by weight:

[0078] 500 parts of cementitious materials, 600 parts of aggregates, 1.5 parts of naphthalene-based water reducer, 2 parts of calcium formate, 1.5 parts of sodium sulfate, 5 parts of diethanolamine, and 2 parts of calcium aluminate.

[0079] Embodiment 3:

[0080] This embodiment is based on Example 1, and the difference from Example 1 is that the weight ratios of sulphoaluminate cement, ordinary cement, ultrafine fly ash and silica fume are different, as follows:

[0081] In this embodiment, the weight ratio of sulphoaluminate cement, ordinary cement, ultrafine fly ash and silica fume is 28:7:2:1.

[0082] Embodiment 4:

[0083] This embodiment is based on the embodiment 1, and the difference from the embodiment 1 is that the formula of the high-performance grouting material contains modified rubber powder. Specifically:

[0084] A high-performance grouting material with both fluidity and strength, composed of the following components in parts by weight:

[0085] 450 parts of cementitious materials, 550 parts of aggregates, 1.2 parts of naphthalene-based water reducer, 2 parts of calcium formate, 1.2 parts of sodium sulfate, 4 parts of diethanolamine, 3 parts of calcium aluminate, and 5.4 parts of modified rubber powder.

[0086] In this embodiment, the added amount of the modified rubber powder is 1.2% of the weight of the gelling material.

[0087] Embodiment 5:

[0088] This embodiment is based on the embodiment 1, and the difference from the embodiment 1 is that the formula of the high-performance grouting material contains modified rubber powder. Specifically:

[0089] A high-performance grouting material with both fluidity and strength, composed of the following components in parts by weight:

[0090] 450 parts of cementitious materials, 550 parts of aggregates, 1.2 parts of naphthalene-based water reducer, 2 parts of calcium formate, 1.2 parts of sodium sulfate, 4 parts of diethanolamine, 3 parts of calcium aluminate, and 6.75 parts of modified rubber powder.

[0091] In this embodiment, the added amount of the modified rubber powder is 1.5% of the weight of the gelling material.

[0092] Comparative Example 1:

[0093] This comparative example is based on Example 1, and the difference from Example 1 is that the formula of the gelling material is different, specifically:

[0094] In this embodiment, the weight ratio of sulphoaluminate cement, ordinary cement, ultrafine fly ash and silica fume is 40:7:3:1.

[0095] Comparative Example 2:

[0096] This comparative example is based on Example 1, and the difference from Example 1 is that the formula of the gelling material is different, specifically:

[0097] In this embodiment, the weight ratio of sulphoaluminate cement, ordinary cement, ultrafine fly ash and silica fume is 30:10:3:1.

[0098] Comparative Example 3:

[0099] This comparative example is based on Example 1, and the difference from Example 1 is that the formula of the gelling material is different, specifically:

[0100] In this embodiment, the weight ratio of sulphoaluminate cement, ordinary cement, ultrafine fly ash and silica fume is 40:10:1:1.

[0101] Comparative Example 4:

[0102] This comparative example is based on Example 1, and the difference from Example 1 is that the formula of the gelling material is different, specifically:

[0103] The cementitious materials are composed of sulphoaluminate cement, ordinary cement and silica fume, and the weight ratio of sulphoaluminate cement, ordinary cement and silica fume is 40:10:1.

[0104] Comparative Example 5:

[0105] This comparative example is based on Example 1, and the difference from Example 1 is that the formula of the gelling material is different, specifically:

[0106] The cementitious material is composed of sulphoaluminate cement and ordinary cement, and the weight ratio of sulphoaluminate cement to ordinary cement is 40:10.

[0107] Comparative Example 6:

[0108] This comparative example is based on Example 1, and differs from Example 1 in that diethanolamine and calcium aluminate are not contained in the formula.

[0109] Comparative Example 7:

[0110] This comparative example is based on Example 1, and differs from Example 1 in that diethanolamine is not contained in the formula.

[0111] Comparative Example 8:

[0112] This comparative example is based on Example 1, and differs from Example 1 in that the formula does not contain calcium aluminate.

[0113] Comparative Example 9:

[0114] This comparative example is based on Example 1, and differs from Example 1 in that an equal amount of calcium chloride is used to replace calcium aluminate.

[0115] Comparative Example 10:

[0116] This comparative example is based on Example 1, and differs from Example 1 in that an equal amount of calcium nitrate is used to replace calcium aluminate.

[0117] Comparative Example 11:

[0118] This comparative example is based on Example 4, and the difference from Example 4 is that the amount of modified rubber powder used is different, specifically:

[0119] A high-performance grouting material with both fluidity and strength, composed of the following components in parts by weight:

[0120] 450 parts of cementitious materials, 550 parts of aggregates, 1.2 parts of naphthalene-based water reducer, 2 parts of calcium formate, 1.2 parts of sodium sulfate, 4 parts of diethanolamine, 3 parts of calcium aluminate, and 4.5 parts of modified rubber powder.

[0121] In this embodiment, the added amount of the modified rubber powder is 1.0% by weight of the gelling material.

[0122] Comparative Example 12:

[0123] This comparative example is based on Example 4, and the difference from Example 4 is that the amount of modified rubber powder used is different, specifically:

[0124] A high-performance grouting material with both fluidity and strength, composed of the following components in parts by weight:

[0125] 450 parts of cementitious materials, 550 parts of aggregates, 1.2 parts of naphthalene-based water reducer, 2 parts of calcium formate, 1.2 parts of sodium sulfate, 4 parts of diethanolamine, 3 parts of calcium aluminate, and 8.1 parts of modified rubber powder.

[0126] In this embodiment, the added amount of the modified rubber powder is 1.8% of the weight of the gelling material.

[0127] The preparation method of the high-performance grouting materials of Example 1 to Example 5 and Comparative Example 1 to Comparative Example 12 refers to the preparation method in the examples, and the grouting materials of Example 1 to Example 5 and Comparative Example 1 to Comparative Example 11 are added with appropriate amount of water and stirred for 10 minutes to obtain uniform slurry, and the fluidity is tested at -5°C respectively; and the grouting material is poured into a channel with a pore diameter of 2 cm and a length of 30 cm, and cured to 28 days. During this period, the compressive strength at 2h, 1d, 2d, 3d and 28d is tested, and the impact strength at 28d is tested. Among them, the fluidity refers to JC / T986-2018 to test the truncated cone fluidity and flow cone fluidity; the compressive strength and impact strength refer to GB / T15231. The results are shown in Table 1:

[0128] Table 1 -5℃ test results

[0129]

[0130] From the data in Table 1, we can see that:

[0131] 1) The amount of diethanolamine used will affect the fluidity of the grouting material. The greater the amount used within the set range, the stronger the fluidity;

[0132] 2) The combination of cementitious materials will affect the fluidity and strength of the grouting material. Silica fume affects the strength, and whether ultrafine fly ash is added and the amount added affect the fluidity of the grouting material;

[0133] 3) The addition of modified rubber powder can improve the impact strength of the grouting material, but it will affect the early strength and 28d compressive strength of the grouting material;

[0134] 4) The combined use of diethanolamine and calcium aluminate will affect the fluidity, strength and 28d compressive strength of the grouting.

[0135] In order to verify the effects of sulphoaluminate cement, alcoholamine reagents and calcium aluminate on the low temperature performance of grouting materials, Example 1, Comparative Example 2, Comparative Examples 6-10 were tested for fluidity, compressive strength and impact strength at -10°C. The results are shown in Table 2:

[0136] Table 2 -10℃ test results

[0137]

[0138] From the data in Table 1 and Table 2, we can see that:

[0139] Aluminate cement, amine reagents and calcium aluminate have a greater impact on the fluidity and early strength of the grouting material at low temperature; but have little effect on the 28d strength; as the temperature decreases, the fluidity and early strength of Example 1, Comparative Example 1, and Comparative Examples 6-8 all decrease, but the degree of decrease is different. Among them, amine reagents have a greater impact on the low-temperature performance of the grouting material.

[0140] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A high-performance grouting material with both fluidity and strength, characterized in that: It includes the following components by weight: 400-500 parts of cementitious materials, 500-600 parts of aggregates, 1.2-1.5 parts of water reducing agent, 2-2.5 parts of early strength agent, 1-1.5 parts of retarder, 2-5 parts of alcoholamine reagents, 2-3 parts of calcium aluminate; The cementitious material is composed of sulphoaluminate cement, ordinary cement, ultrafine fly ash and silica fume; the particle size of the ultrafine fly ash is 1 to 5 microns; The weight ratio of the sulphoaluminate cement, the ordinary cement, the ultrafine fly ash and the silica fume in the cementitious material is (28-41): (7-10): (2-3): 1; It also includes rubber powder; the amount of the rubber powder added is 1.2-1.5% of the weight of the gelling material; the rubber powder is modified rubber powder obtained by modification with a silane coupling agent; The high-performance grouting material is used for grouting of concrete structures at -5 to -10°C.

2. A high-performance grouting material having both fluidity and strength according to claim 1, characterized in that: The early strength agent is calcium formate.

3. A high-performance grouting material having both fluidity and strength according to claim 1, characterized in that: The water reducing agent includes a naphthalene-based water reducing agent.

4. A high-performance grouting material having both fluidity and strength according to claim 1, characterized in that: The aggregate is quartz sand, which includes coarse sand and fine sand. The particle size of the coarse sand is 2.0-2.5 mm, the particle size of the fine sand is 0.5-0.8 mm, and the weight ratio of the coarse sand to the fine sand is 1:(0.3-0.5).

5. The method for preparing a high-performance grouting material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, mixing the ultrafine fly ash, the silica fume, the aggregate and the early strength agent uniformly to obtain material A; S2, mixing the sulphoaluminate cement and the calcium aluminate uniformly, adding them to the material A, and mixing them uniformly to obtain material B; S3, adding the water reducer and the retarder to the material B and mixing evenly to obtain material C; S4. Add the alcoholamine reagent into the material C and mix evenly to obtain a high-performance grouting material.

6. The use of the high-performance grouting material according to any one of claims 1 to 4, characterized in that: The high-performance grouting material is used for grouting of concrete structures at -5 to -10°C.

Citation Information

Patent Citations

  • High-performance cement-based grouting material

    CN108558335A

  • Cement grouting material, preparation method and applications thereof

    CN110467394A

  • Carbon fiber high-performance grouting material and preparation method thereof

    CN118307275A